How sophisticated servicescape can reduce negative feelings when a failure occur? - Terres, Mellina (2022)
Terres, M., Herter, M., Pinto, D. C., & Mazzon, J. A. (2018). How sophisticated servicescape can reduce negative feelings when a failure occur? . In SERVSIG Conference Proceedings, 2018: Opportunities for Services in a Challenging World (pp. 420-429). [10th SERVSIG, 2018,14-16 june 2018, Paris, France]. SERVSIG. ISBN: 978-2-9516606-3-2